The "tolerant chimpanzee"—towards the costs and benefits of sociality in female bonobos. (4th September 2018) - Nurmi, Niina O; Hohmann, Gottfried; Goldstone, Lucas G; Deschner, Tobias; Schülke, Oliver
Abstract : How group-living animals compete over food is also thought to affect how they socialize beyond the feeding context. We found female bonobos to cooperate aggressively mainly against males, and dominance rank to exhibit effects on food intake and feeding effort. Although these rank effects did not translate into variation in physiologically measured energy balance, the results suggest that increased female social tolerance evolved in bonobos to enhance cooperation against males in discrete food patches. Abstract: Humans share an extraordinary degree of sociality with other primates, calling for comparative work into the evolutionary drivers of the variation in social engagement observed between species. Of particular interest is the contrast between the chimpanzee ( Pan troglodytes ) and bonobo ( Pan paniscus ), the latter exhibiting increased female gregariousness, more tolerant relationships, and elaborate behavioral adaptations for conflict resolution. Here, we test predictions from 3 socioecological hypotheses regarding the evolution of these traits using data on wild bonobos at LuiKotale, Democratic Republic of Congo. Focusing on the behavior of co-feeding females and controlling for variation in characteristics of the feeding patch, food intake rate moderately increased while feeding effort decreased with female dominance rank, indicating that females engaged in competitive exclusion from high-quality food resources. However, these rank effects did not translate into variation in energy balance, as measured from urinary C-peptide levels. Instead, energy balance varied independent of female rank with the proportion of fruit in the diet. Together with the observation that females join forces in conflicts with males, our results support the hypothesis that predicts that females trade off feeding opportunities for safety against male aggression. The key to a full understanding of variation in social structure may be an integrated view of cooperation and competition over access to the key resources food and mates, both within and between the sexes.